Follow-up survey of oral health status of children enrolled in UNRWA schools: a cross-sectional study. (March 2019) - Hababeh, Majed; Matooq, Amjad; Odattalla, Abdalla; Na'jeh, Asa'ad; diab, Hanan; Burbara, Imad; khoury, Amjad; Saleh, Zaki; Ayoub, Ayoub; Salameh, Mohammad; Hadi Saleh, Mohammad; Khader, Ali; et al.
Abstract: Background: The United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) School Health Programme provides preventive oral health services to school students through regular dental screening of new entrants and fourth and seventh grade students, in addition to the health education activities and treatment of decayed teeth provided by dental surgeons in health centres and by mobile dental teams. The main focus of UNRWA oral health services continues to be prevention rather than treatment. The objective of this follow-up survey was to calculate decayed, missing, and filled teeth (DMFT), and decayed, missing, and filled surfaces (DMFS) indices among seventh grade UNRWA schoolchildren in all five areas in which UNRWA operates (Gaza, Jordan, Lebanon, Syria, and West Bank), and to compare the results of this survey globally, locally and with a previous survey conducted in 2010 and 2011. Methods: A cross-sectional survey was conducted by calibrated examiners between March, 2016, and May, 2016. Two-stage sampling was used, with schools selected during the first stage and classes selected in the second stage. The sample size was calculated based on the number of students registered in each area. The confidence level was 95%, power 80%, and precision 5%. A total of 1550 children participated (100% response rate), 383 in Jordan, 390 in Lebanon, 340 in West Bank, and 437 in Gaza. All participants provided verbal informed consent. Data were analysed using Epi Info 7. Multiple logistic regression was used to analyse caries experience, prevalence of caries, and the most relevant behavioural and sociodemographic indicators. A p value of less than 0·05 was considered statistically significant. Findings: The prevalence of dental caries among examined children was 72·8% (1129 of 1550; 95% CI 70·5–75·0); the highest prevalence was in the West Bank (79·7%; 271 of 340) and lowest was in Jordan (68·4%; 262 of 383). The prevalence of untreated decayed surfaces was 69·4% (1076 of 1550; 95% CI 67·0–71·7); the highest prevalence was in the West Bank (76·8%; 261 of 340) and lowest was in Jordan (64·0%; 245 of 383). The percentage of children with one or more sealed permanent teeth was 9·8% (8·4–11·4), compared with 6·8% in 2011, and with wide variation between areas; the highest prevalence was in Lebanon (31.5%), while in Gaza and the West Bank the prevalence was less than 2·0%. The percentage of children who did not use a toothbrush and toothpaste was 19·1%, compared with 22·0% in 2011. The percentage of children who cleaned their teeth after every meal was 59·3% (919 of 1550), compared with 31·6% in 2011. Overall, 18·3% (284 of 1550) of children had never attended a dentist, and 83·1% (1289 of 1550) had experienced toothache in the past. In the total sample, 66·0% (1022 of 1550) of children were used to drinking soft drinks during meals. This habit was less frequent in Gaza (37·5%; 164 of 437) than in Jordan (71·1%; 272 of 383), the West Bank (75·0%; 255 of 340), and Lebanon (75·0%; 292 of 390). Interpretation: The prevalence of dental caries remains very high in Palestinian refugee school children, of whom only 27·2% are free of caries. The high percentage of untreated dental caries and the low percentage of sealed teeth call for increased efforts, refinement, and completion of the preventive strategies of the UNRWA. The main behavioural factors relating to the prevalence and severity of caries were frequency of sugar intake between meals and soft drink consumption. Funding: None.